Structure Evolution of Thermotropic Polymers by Thermal Annealing. A Light and X-Ray Scattering Study. Issue 1765 (1st October 2015) - Reyes-Mayer, Adriana; Romo-Uribe, Angel; Jaffe, Michael
ABSTRACT: Small-angle light scattering (SALS) and wide-angle X-ray scattering (WAXS) were used to study the influence of heat treatment on the texture and microstructure of extruded films of high-performance thermotropic liquid crystal polymers (LCPs). The microstructure was correlated with tensile mechanical properties. LCPs based on random units of hydroxybenzoic acid (B), hydroxynaphthoic acid (N), terephthalic acid (TA) and biphenol (BP) were supplied by the former Hoechst Celanese Corp. as 50 μm thick extruded films. The LCPs, denoted B-N, COTBP and RD1000, have B and N as common co-monomers and vary the other co-monomers. Thus, this study also enabled the investigation of the influence of monomer composition on microstructure and mechanical properties. Heat treatments were carried out at temperatures close to the solid-to-nematic transition ( Ts→n ) for periods up to 5 h, under dry air conditions. The thermal treatment produced either two endotherms or a small increase of Ts→n (B-N and RD1000), or Ts→n increased significantly (COTBP). Moreover, when heat treatment was carried out approximately 40°C below the respective Ts→n, the mechanical Young's modulus, E, along the extrusion axis increased for all LCPs. Strikingly, for COTBP, E increased over 100% relative to the as-extruded film. The results also showed that the optimum treatment time for improving the Young modulus was between 3 and 4 h. Wide-angle X-ray scattering showed a significant sharpening of crystalline reflections and concentration of the 002 meridional reflection as a result of thermal treatment, suggesting the elimination of defects and a better alignment of the molecular chains along the extrusion axis. This would explain the increase in tensile modulus.